Verification of selected methods of assessing the financial situation of a company - Pitera, Rafał (Weryfikacja wybranych metod oceny sytuacji finansowej przedsiębiorstwa, 2019)
The article attempts to evaluate selected diagnostic tools classified as early warning methods. They are usually used to assess the current financial condition of a company, they are also used to predict bankruptcy. The most popular methods were verified, namely discriminant models, logit models and scoring models. Based on the collected financial data of enterprises that in 2010-2016 declared liquidation bankruptcy and their healthy counterparts, the usefulness of individual models was assessed in terms of the reliability of the results obtained. The analysis shows that the scoring model was the most effective in assessing the financial situation. Discrimination models came the second in this respect. Logit models proved to be the least effective. All the models used in the study were characterized by a level of accuracy of forecasts above 50%, which indicates a good result. The conducted study confirms the legitimacy of using such tools. They are also evidence of the continuing popularity of early warning models among people assessing the financial situation in an enterprise
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 41-51
Keywords: methods of early warning; bankruptcy of enterprises; financial analysis; modele wczesnego ostrzegania; upadłość przedsiębiorstwa; analiza finansowa